Diversity of the genus Camellia L. (Theaceae) in Lam Dong province - Hoi, Quach Van; Dung, Luong Van; Doudkin, Roman V.; Chung, Bui Danh; Duy, Nong Van (Academia Journal of Biology, 2021)
Through field survey and morphological research, this study has determined that the Camellia genus in Lam Dong province, Vietnam has a high diversity of morphological, distribution and taxa characteristics. The species of Camellia genus in Lam Dong province are mostly shrubs and small trees. The narrow oblong leaves are a very common and typical characteristic for Camellia in Lam Dong province. The flowers of the species of Camellia are diverse with four main colours is white, yellow, pink and purple. The fruits are globose, flattened globose, wrinkled or uneven edges. Especially, the obovoid fruit only occurs in Lam Dong province. Most of the species of Camellia genus in this province are endemic. The study has added ten species of the Camellia genus, brings the total of species of Camellia genus to Lam Dong province to between sixteen and twenty six. This is the first study to evaluate Camellia diversity in Lam Dong province. It is also the first complete statistics on the number of species of Camellia genus in Lam Dong province to confirm that this province is the second diversity centre of Camellia of Vietnam following the first centre in the North of Vietnam.